Urgensi Mutu Pelayanan Customer Service Dalam Meningkatkan Kepuasan Dan Loyalitas Nasabah - Umatin, Choiru; Vanessa, Chelsea; Sulkha, Atina; Nurkholifah, Noviana; Pambudi , Adjie; Al Muiz, Mochamad Nasichin; Ridwanulloh, M. Ubaidillah (WADIAH, 2024)
ABSTRACT Service capability plays an important role for the sustainability of a company in increasing customer satisfaction and loyalty. The main priority of a company engaged in banking services is customer satisfaction. In winning the increasingly competitive competition, the Bank strives to provide the best service (service excellent). This study aims to determine the importance of retaining customers and reaching potential customers. In addition, to find out how to maintain and improve the quality and loyalty of its customers. The research uses a library research method in which data is collected based on academic data bases, digital libraries, and repositories of educational institutions. Some references are obtained from books, scientific journals, articles and research reports relevant to customer service quality research in improving customer quality and loyalty. The result is that customer service quality has a crucial role in shaping customer perceptions of financial institutions. Quality of service is very concerned about satisfaction and loyalty to maintain a positive brand image or image in the eyes of the community. The effect of customer satisfaction on customer loyalty can show that customer satisfaction has a significant effect on customer loyalty. Increasing service quality has an impact on customer satisfaction and loyalty is also increasing. Conversely, if the quality of Customer Service service decreases, it will have an impact on worsening customer satisfaction and loyalty.